2005
DOI: 10.1097/00006982-200501000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Comfort Care on the Pain Response in Preterm Infants Undergoing Screening for Retinopathy of Prematurity

Abstract: ROP screening is very distressful for preterm infants. The routine use of comfort care to reduce pain during the examination could not be supported by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 10 publications
2
58
0
2
Order By: Relevance
“…Although results of a meta-analysis of 4 studies conducted during eye examination showed sucrose significantly reduced Premature Infant Pain Profile (PIPP) scores, the effects were small and inconsistent between individual studies. [51][52][53][54] In addition, a 50% glucose solution was no more effective than water during circumcision, 55 and a single dose of sucrose failed to significantly reduce crying in older infants undergoing urethral catheterization 56 and venepuncture. 57 The reduced effectiveness of sweet solutions in these more invasive procedures of relatively long duration may be due to the shortlasting effects of a single dose given 2 minutes before the procedures.…”
Section: Human Model Studiesmentioning
confidence: 99%
“…Although results of a meta-analysis of 4 studies conducted during eye examination showed sucrose significantly reduced Premature Infant Pain Profile (PIPP) scores, the effects were small and inconsistent between individual studies. [51][52][53][54] In addition, a 50% glucose solution was no more effective than water during circumcision, 55 and a single dose of sucrose failed to significantly reduce crying in older infants undergoing urethral catheterization 56 and venepuncture. 57 The reduced effectiveness of sweet solutions in these more invasive procedures of relatively long duration may be due to the shortlasting effects of a single dose given 2 minutes before the procedures.…”
Section: Human Model Studiesmentioning
confidence: 99%
“…18,19 A few investigators have examined ways to reduce the stress and pain of the ROP examination, with variable results; nesting was shown to reduce the discomfort of the examination, 2 whereas comfort care and oral sucrose have not conclusively shown a reduced pain response. [20][21][22] The use of topical anesthetic in each eye before the onset of the examination 23 and performing the examination as quickly as possible are recommendations to decrease the pain and distress of the examination. A few reports in the literature have examined the anticholinergic effects of mydriatic eye drops on gastrointestinal function, with feeding difficulties seen on the day of the dilated ophthalmologic examination.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reviewed studies included a variety of procedures, the majority involved heel lance for routine blood draws. The authors of the Cochrane study also carried out a systematic review of 5 published articles, [21][22][23][24][25] summarized in e-Supplement 1 (available at jaapos.org), on the effect of sucrose during ROP assessment in premature infants. The pooled results indicated that oral sucrose did not cause a significant reduction in PIPP scores in premature infants undergoing eye ROP assessments (weighted mean difference À0.65 [95% CI, À1.88 to 0.59]).…”
Section: Sucrose Feeding and Nonnutritive Suckingmentioning
confidence: 99%